Organizational Communication Strategy of Forest Management in Mundeh Kauh Village, Selemadeg District, Tabanan - Rochimah, Haris Annisari Indah Nur (COMMUSTY Journal of Communication Studies and Society, 2023)
In general, communication occurs in a particular situation. The process of communication, of course, requires a communication strategy. A communication strategy is essential in the organization, as it aims to plan work programs to be carried out correctly to achieve the expected goals. Good communication can increase motivation, and the information conveyed can be well received, improving performance. Social Forestry Organization As an organization that regulates forest management under the auspices of the Environment and Forestry Service, it is obligated always to be prime in performance and community service. Therefore, the Social Forestry Organization is aware that it is necessary to take concrete steps to improve the quality of communication between group members and leaders. This study aims to determine the organization's communication strategy and how it is carried out to achieve the goal. The research results obtained by drawing this conclusion are organizational communication strategies that are very well established between members of the organization and leaders.